First: eliminate parenthesis > use the Foiling method....
[(3)(3) + (3)(4i)] + [(4i)(3) + (4i)(4i)]
Sec: combine the terms...
[9 + 12i] + [12i + 16i^2]
9 + 12i + 12i + 16i^2
Third: combine "like" terms...
9 + 24i + 16i^2
*The i^2 becomes -1 >>> replace -1 with i^2.....
9 + 24i + 16(-1)
9 + 24i - 16
= - 7 + 24i
2007-01-28 09:10:42
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
(3+4i)(3+4i)
= 9 +12i +12i +16i^2
= 9 + 24i -16
= -7 +241
2007-01-28 08:41:11
·
answer #2
·
answered by ironduke8159 7
·
0⤊
0⤋
(3 + 4i)(3 + 4i)
= 3² + 2*3*4i + 16i²
i² = -1
= 9 + 24i + 16(-1)
= 24i - 7
2007-01-28 08:38:06
·
answer #3
·
answered by Tom :: Athier than Thou 6
·
0⤊
0⤋
(3 + 4i)(3 + 4i) = 9 + 12i + 12i + 16i^2 = 9 + 24i - 16 = -7 + 24i
2007-01-28 08:36:50
·
answer #4
·
answered by DavidK93 7
·
0⤊
0⤋
(3+4i)(3+4i) = (4i+3)(4i+3)
(4i+3)(4i+3) = 16i^2 + 12i +12i + 9
16i^2 + 12i +12i + 9 = 16i^2 + 24i +9
sixteen i squared, plus twenty-four i, plus nine
2007-01-28 08:42:44
·
answer #5
·
answered by charlie 1
·
0⤊
1⤋
(3+4i)(3+4i)
9+12i+12i+16i^2
9+ 24i+16i^2
2007-01-28 08:37:45
·
answer #6
·
answered by music_gurl62091 2
·
0⤊
0⤋
merely to diminish back-up what you've already been advised....this would't be solved, in user-friendly words simplified. get rid of the brackets and combine like words: (2+3i)-(-3+4i)? 2 + 3i + 3 - 4i 5 - i..........answer
2016-12-03 04:05:18
·
answer #7
·
answered by lesniewski 4
·
0⤊
0⤋
again FOIL first
9+12i+12i+16i^2
combine like terms
9+24i+16i^2
i^2=-1
so 9+24i+16(-1)
9+24i-16...
-7+24i....final answer
2007-01-28 08:37:09
·
answer #8
·
answered by dla68 4
·
0⤊
0⤋
9+12i+12i+16i^2
9+24i+16(-1)
9+24i-16
24i-7
2007-01-28 08:42:16
·
answer #9
·
answered by k j 1
·
0⤊
0⤋
ok what the problem ? The expression evaluates to 24i - 7 but besides that...
2007-01-28 08:38:11
·
answer #10
·
answered by walter_b_marvin 5
·
0⤊
2⤋